Islamic Renewal in the Field of Family Law: A Historical Analysis of Gender Equality - Qadri, Busran; Siregar, Ihsan Mulia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This paper aims to discuss Islamic renewal in the field of family law by focusing on gender equality. The unfair treatment of women within pre-Islamic Arabian society was the starting point for Islamic renewal in the field of law, especially of family law. Such treatment was not in line with the principles contained in Islam, i.e., to bring mercy to all worlds. This study used a normative descriptive-analytical method and a sociological-historical approach. The data analyzed came from articles, books, and various references related to the topic. The study concludes that as a religion that brings mercy to all people, Islam reforms the behaviors detrimental to women; yet, the reform is not the end result, in which it is highly likely that it will be updated in the future for the benefit of the community universally. Therefore, a comprehensive understanding is needed in understanding Islamic law related to gender relations between men and women. This study also reveals that socio-historically men and women have a balanced and equal relationship with each other.